Oxidative amidation by Cu(ii)–guanidine acetic acid immobilized on magnetized sawdust with eggshell as a natural base. (30th June 2020) - Darvishi, Atefeh; Kazemi Miraki, Maryam; Arefi, Marzban; Heydari, Akbar
Abstract : Copper(ii )–guanidine acetic acid complex was immobilized on the surface of magnetized raw waste sawdust (SD) as an abundant natural biopolymer and employed as an efficient and recoverable catalyst in oxidative amidation reaction, while waste eggshell (ES) powder was used as a low-cost solid base. Abstract : Copper(ii )–guanidine acetic acid complex was immobilized on the surface of magnetized raw waste sawdust (SD) as an abundant natural biopolymer and employed as an efficient and recoverable catalyst in oxidative amidation reaction, while waste eggshell (ES) powder was used as a low-cost solid base. The magnetic raw catalyst was fully characterized using FTIR, XRD, SEM, EDX, TGA, and VSM. A variety of amide derivatives were successfully synthesized in moderate to good yields using benzyl alcohol and amine salts. The application of sawdust and eggshell as two natural and abundant waste materials is the main advantage of this research. Moreover, these low-cost catalysts were recovered at least five times and utilized in reaction systems with a minimal decrease in activity.